Neuronal microcircuits for decision making in C. elegans - Faumont, S (2012)
The simplicity and genetic tractability of the nervous system of the nematode Caenorhabditis elegans make it an attractive system in which to seek biological mechanisms of decision making. Although work in this area remains at an early stage, four basic types paradigms of behavioral choice, a simple form of decision making, have now been demonstrated in C. elegans. A recent series of pioneering studies, combining genetics and molecular biology with new techniques such as microfluidics and calcium imaging in freely moving animals, has begun to elucidate the neuronal mechanisms underlying behavioral choice. The new research has focussed on choice behaviors in the context of habitat and resource localization, for which the neuronal circuit has been identified. Three main circuit motifs for behavioral choice have been identified. One motif is based mainly on changes in the strength of synaptic connections whereas the other two motifs are based on changes in the basal activity of an interneuron and the sensory neuron to which it is electrically coupled. Peptide signaling seems to play a prominent role in all three motifs, and it may be a general rule that concentrations of various peptides encode the internal states that influence behavioral decisions in C. elegans.